The Influence of Work Capability and Commitment on the Performance of Tourism Aware Group Managers in Paser District with Innovative Work Behavior as an Intervention Variable - Ika Marsilia; Meutia; Safitri, Julia (International Journal of Asian Business and Management, 2023)
This research aims to determine the influence of work capability and commitment on the performance of tourism awareness group administrators in Paser Regency with innovative work behavior as an intervening variable. The data analysis used is path analysis and multiple regression analysis using smart PLS. The research results show that capability has no effect on performance, because the test results are based on a P value of 0.638 (>0.05) and a statistical T value of 0.471 (<1.96), work commitment has a significant effect on performance, with test results on the P value of 0.045 (< 0.05) and statistical T value of 2.008 (> 1.96), innovative work behavior has no significant effect on performance, with test results showing a P value of 0.279 (> 0.05) and a T statistical value of 1.084 (< 1.96), work commitment has a significant effect on innovative work behavior, with test results on a P value of 0.045 (< 0.05) and a statistical T value of 2.005 (> 1.96), capability does not have an effect on performance through innovative work behavior, with a P value of 0.309 (> 0.05) and a statistical T value of 1.018 (< 1.96), work commitment has no effect on performance through innovative work behavior, with a P value result of 0.426 ( > 0.05) and a statistical T value of 0.796 (< 1.96)